Evaluating Focus and Quality of Indonesian E-Government Websites - Fathul Wahid (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2008)
The study aimed to evaluate focus and quality of Indonesian e-government website. All 456 websites ofdistricts/cities throughout the country are taken into account. The study revealed that 66.9% of districts/citieshad their own website and were in operations, while other were either still embedded into website of province,not found, or inaccessible. In general, the websites focused on promoting linkage between government andbusiness, while efficiency and effectiveness in the delivery of frontline services were less prioritized. The qualityof the website in general was in medium level, both in terms of the quality of content and the level of ease-of-use.Keywords: e-government website, website focus, website quality, Indonesia.